Report on professional attachment with Citigroup Asset Management. - Tan, Wee Chuan. (2008)
During the attachment, author participate in the intranet content development for training, as well as the preparation of training materials for a wide variety of investment products. He also helped out the sales team in the preparation of sales materials and generation of sales ideas.